Desain Ulang Struktur Bawah Bangunan Studi Kasus: Gedung Kantor DPRD Dharmasraya Provinsi Sumatera Barat - Jihan Melasari; Meri Sufina; Afdhal Yusra (Civil Engineering Collaboration, 2021)
Solid construction certainly has a strong foundation that sustain Minimizing the potential for a settlement and the destruction of the foundation is so important to be known. So we should be able to know exactly how large a bearing capacity of the foundation. The purpose of this thesis is to redesign the foundation witha bore pile foundation. So in terms of knowing the size of the bearing capacity of the foundation, ,we discusses how the value of the bearing capacity of the foundation analytically which in this case using mayerhoff method, the from data SPT will using reese & wright method and mayerhoff method. The value of bearing capacity that we seek to determine the strength of the foundation that suffer a load the which is located thereon. legislative officebuilding Dharmasraya using a pile foundation and design with bore pile foundation, At the point BH-1 the carrying capacity of the single pile foundation is greater than the load, the foundation is said to be safe, Q permits> the rated load is 2000,32 tons > 47,973 tons. At point BH-2 the bearing capacity of the pile foundation of the group is greater than the load, the foundation is said to be safe, Q permits > 2073,532 tons > 1218,989 tons. At point BH-1 the carrying capacity of single bore pile foundation is greater than load carrying, the foundation is said to be safe, Q permit> the mean load is 1230,249 tons > 47,973 tons. At BH-2 point thecarrying capacity of the bore pile foundation is larger than the load, the foundation is said to be safe, Q permits> the rated load is 1222,337 tons > 1218,989 tons.